PENGARUH CAHAYA TERHADAP PERTUMBUHAN DAN PERKEMBANGAN TANAMAN KACANG HIJAU - Darma Taksiah; Sari Safira; Suci Ramadani (JOURNAL SAINS STUDENT RESEARCH, 2025)
The objective of this study was to examine how light intensity affects the growth of mung bean plants (Vigna radiata) by comparing three different lighting conditions: plants exposed to direct sunlight, plants kept in a dimly lit indoor environment, and plants placed inside a closed cardboard box with no light exposure at all. The research method used was direct observation over a period of seven days, during which the physical condition and stem height of the plants were recorded daily. The results showed that plants grown indoors without direct sunlight grew more slowly and had paler leaves. Meanwhile, the plants that received no light at all exhibited signs of etiolation, characterized by rapid but weak stem elongation and pale leaf color. These findings confirm that light is a crucial factor in the photosynthesis process and significantly influences plant growth quality. This study reinforces the theory that plant height alone is not a reliable indicator of successful growth; stem strength and leaf color must also be considered. The results of this research are expected to serve as a valuable learning experience for students and the general public regarding the importance of light exposure in plant cultivation.